Clinicopathologic features, management and outcome of ten cases of gastrointestinal stromal tumors (IMC Journal of Medical Science, 2017)
Background and objectives: Gastrointestinal stromal tumor (GISTs) is an uncommon and rare disease in Bangladesh. Our aims were to describe socio-demographic characteristics, clinical presentations, anatomical location, morphological variation, treatment and outcome of GIST in ten cases.Methods: This study included consecutive ten cases of GISTs diagnosed and treated in two tertiary level hospitals in Dhaka, Bangladesh from 2013 to 2016. Patients socio-demographic characteristics, clinical presentations, anatomical location, histological types, presence of CD117 markers were determined. Outcome of the treatment by surgical intervention and imatinib mesylate (400mg/day) were evalauted.Results: Total 10 patients were included in the study. Among them 6 were male and 4 were female. The age range was 32-74 years. Abdominal pain, haematemesis, melaena, haematochezia and anaemia were the most common presentation. One patient had dysphagia and another had features of subacute intestinal obstruction. Five patients had GIST in the stomach (50%), two had in colon and one in esophagus, duodenum and ileum respectively. CD 117 was positive in 8 cases, majority had spindly type cell with low mitotic figure. Imatinib therapy was given in all the cases except two patients. Disease recurrence in the form liver metastasis was found in two cases and both died. Disease free survival for more than 2 years was observed in 4 cases.Conclusion: Haematemesis and melaena were common presentation of GISTs. Stomach was the most common site for GISTs and majority had spindle type of cells and positive CD117 marker. Surgical intervention and imatinib therapy was found effective.IMC J Med Sci 2017; 11(2): 45-49